కవిజనాశ్రయము-ఛందశ్శాస్త్రము - Vemulavada Bheema Kavi (CIIL-Mysuru, 1917)
It is the First Chando Grantha in Telugu. This book authorship has different opinions in Telugu Literature from the beginning. This book was edited by Jayanti Ramaiahpantulu and published by Andhra Sahitya Parishat, Kakinada in 1917 in the name of Vemulavada Bheemakavi. So many discussions about this book authorship taken place. Recently some of the critics observations that Malliya Rechana (940B.C) is the Author of this book through the literary and inscriptions (Kurkyala Inscription) evidences.
Kavijanaashrayamu-Chandassaashtramu
Keywords: Telugu Prosody; Telugu